Waste management in healthcare: during and beyond a global pandemic - Lechner, Matt; Harrap, Iona; Emanuel, Oscar; Eynon-Lewis, Nick (BMJ leader, 2023)
Sustainability is of course a topic and goal of intimidating size. Addressing all its aspects would require a team far larger than ours and would be well-beyond the scope of our article. However, the key tenets of leadership can be applied to waste management within the overall field of sustainability. The management of physical waste is an interesting topic to address from a leadership perspective because it is carried out by every individual frontline healthcare worker multiple times a day, with policy made at local and national levels. As such, we should use leadership principles or frameworks aimed at all staff and take into account their personal responsibilities as executors of the NHS’ sustainability goals.